Pemberdayaan Masyarakat Melalui Optimalisasi Pariwisata PendidikanStudi Kasus Program Pengabdian Awardee Kelurahan LPDP UGM di Desa Kalipucung, Kabupaten Semarang - Ishak, Muhammad; Maulana, Ahmad Reza; Salafudin, Agus (Sagu: Jurnal Pengabdian Masyarakat, 2025)
This article explores the implementation and impact of the "Awardee Merakyat" community empowerment program conducted by Kelurahan LPDP UGM in Dusun Kalipucung, Semarang Regency, from November 1-3, 2024. Employing a qualitative descriptive approach with the Participatory Rural Appraisal (PRA) method, the study emphasizes community participation in the development of educational tourism as a sustainable village empowerment strategy. The program focused on strengthening local capacity through educational outreach (scholarship socialization), entrepreneurial training (branding and digital marketing for local products), youth organizational development (Karang Taruna), health promotion, and provision of tourism-supporting infrastructure. The findings reveal significant improvements in community motivation, skills, and ownership over local resources, laying the groundwork for Kalipucung's transformation into an educational tourism village. The study concludes that participatory and context-based empowerment models can serve as effective frameworks for inclusive and sustainable rural development, highlighting the potential for replication in other localities with contextual adjustments.